Predictive validity of the prognosis on admission aneurysmal subarachnoid haemorrhage scale for the outcome of patients with aneurysmal subarachnoid haemorrhage - Tuan Anh Nguyen; Luu Dang Vu; Ton Duy Mai; Co Xuan Dao; Hung Manh Ngo; Hai Bui Hoang; Son Ngoc Do; Hao The Nguyen; Dung Thi Pham; My Ha Nguyen; Duong Ngoc Nguyen; Hien Thi Thu Vuong; et al. (Scientific Reports, 2023)
Abstract This multicentre prospective cohort study aimed to compare the accuracy of the PAASH, WFNS, and Hunt and Hess (H&H) scales in predicting the outcomes of adult patients with aneurysmal SAH presented to three central hospitals in Hanoi, Vietnam, from August 2019 to June 2021. Of 415 eligible patients, 32.0% had a 90-day poor outcome, defined as an mRS score of 4 (moderately severe disability) to 6 (death). The PAASH, WFNS and H&H scales all have good discriminatory abilities for predicting the 90-day poor outcome. There were significant differences in the 90-day mean mRS scores between grades I and II (p = 0.001) and grades II and III (p = 0.001) of the PAASH scale, between grades IV and V (p = 0.026) of the WFNS scale, and between grades IV and V (p < 0.001) of the H&H scale. In contrast to a WFNS grade of IV–V and an H&H grade of IV–V, a PAASH grade of III–V was an independent predictor of the 90-day poor outcome. Because of the more clearly significant difference between the outcomes of the adjacent grades and the more strong effect size for predicting poor outcomes, the PAASH scale was preferable to the WFNS and H&H scales.